In the Carquinez Woods - Harte, Bret, 1836-1902 (Salt Lake City, UT : Project Gutenberg, 2006)
"In the Carquinez Woods" by Bret Harte is a novel written during the late 19th century. The book explores themes of survival, human relationships, and the contrasts between civilization and nature, primarily through the experiences of its characters in a remote California forest. The opening chapter introduces two main characters: a mysterious young man, referred to as Low, and a woman named Teresa, who is escaping from her troubled past, including a violent confrontation with law enforcement. The beginning of the story establishes a vivid and atmospheric setting in the dense and shadowy Carquinez Woods, where the sense of isolation becomes palpable. As night falls, Teresa emerges as a strong yet troubled figure who grapples with her actions and the implications of her past while hiding from the law. The young man, who seems to embody the spirit of the wilderness, encounters Teresa and their dynamic begins to evolve. Tension arises as they navigate their uncertain circumstances, hinting at deeper connections and personal struggles. The narrative sets the stage for a complex interplay between their pasts and their potential for redemption, all within the backdrop of a hauntingly beautiful yet foreboding natural environment. (This is an automatically generated summary.)
Release date is 2006-05-17
Produced by Donald Lainson; David Widger
Keywords: American fiction -- 19th century; California -- History -- 19th century -- Fiction; Man-woman relationships -- Fiction; Gold mines and mining -- California -- Fiction